Estimation of vitamin B12 in plasma by High Performance Liquid Chromatography - Hasnat, Fahmida; Bhuiyan, Habiba Akhter; Misbahuddin, Mir (Bangladesh Journal of Pharmacology, 2017)
High performance liquid chromatography was used to develop and validate the detection of vitamin B12 in blood plasma sample. The mobile phase consists of a mixture of 0.025% trifluroacetic acid in deionized water and 30% methanol. The mixture used was adjusted to pH 2.9 and the flow rate was adjusted to 0.5 mL/min. The separation was achieved using C18 column maintained at 30ºC temperature and detection of vitamin B12 was conducted at maximum wavelength 230 nm. Video Clip of Methodology: Estimation of vitamin B12 in plasma by HPLC: 4 min 29 sec Full Screen Alternate